Effect of Real-Time Environment on Mechanical Properties of Preformed Stainless Steel Archwires: An In Vivo Study - Divya Pai; Arun S. Urala; Kishore Ginjupalli; Kalyana Chakravarthy Pentapati; Gaurav Agrawal (The Scientific World Journal)
Introduction. Clinicians should be aware of any effect the oral environment may have on archwires. Laboratory models fail to closely imitate intraoral conditions. The aim was to evaluate the change in mechanical properties of preformed stainless steel archwires after 15 weeks of exposure to the oral environment. Methods. Three commercially manufactured 0.019 × 0.025″ stainless steel archwires were evaluated. Young’s modulus, yield strength, spring factor, and hardness were studied. The unexposed distal end cuts (control samples) and archwires were tested after 15 weeks of intraoral exposure (test samples). Tension tests, Vickers microhardness tests, and nanoindentation tests were carried out. Results. Normality was tested using the Shapiro–Wilk test. Statistical analyses included the paired t-test for intragroup comparisons and Kruskal–Wallis ANOVA with the post hoc Dunn test for comparison of mean percentage reduction in values. At T15, Young’s modulus showed a statistically significant decrease. Changes in yield strength and spring factor were not significant for groups other than American Orthodontics wires. The reduction in hardness was significant in 3M Unitek. Vickers, tension, and nanoindentation tests demonstrated an expansive range between hardness and Young’s modulus so determined. Conclusion. 3M Unitek archwires showed the highest difference in Young’s modulus. Yield strength values increased in Ortho Organizers archwires. Spring factor decreased only in 3M Unitek archwires. Hardness values obtained from various tests did not produce identical results.